Power System Oscillation Damping Using New Facts Device - D. Narasimha Rao; V. Saritha (Institute of Advanced Engineering and Science, 2015)
This paper presents about improving stability of the system which can be possible with new FACTS device with more convenient. FACTS devices come under the influence of power electronics equipment. Distributed Power Flow Controller is a FACTS device used for damping low frequency oscillation with new controlling approach. It is valid for a wide range of the operating condition. In this work explain the basic model and its steady state operation, mathematical analysis injection of current control model of the DPFC. Using damping controller used in DPFC facts device as input to implement the task of power oscillation damping .Here this work had a brief study on damping, terminal voltage and excitation voltage at different load conditions, simulation results demonstrate damping low frequency oscillation at nominal, light and heavy loading conditions